2015
DOI: 10.1016/j.jval.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Health Utility Values Associated with Surgical Site Infection: A Systematic Review

Abstract: SSI may substantially affect patients' health utility and needs to be considered when modeling decision problems in surgery. The evidence base for SSI utilities is of questionable quality and skewed toward orthopedic surgery. Further research must concentrate on producing reliable estimates for patients without orthopedic problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 84 publications
2
52
1
1
Order By: Relevance
“…EQ-5D scores demonstrated that SSIs negatively impact on patient HRQoL, demonstrated by a statistically significant reduction in HRQoL scores (11%) at 30 days in patients who underwent laparotomy surgery, relative to patients who did not develop an SSI [9]. It is noteworthy that the results of this study were also included in a recent systematic review by Gheorghe et al, who reported that the SSI utility decrement in patients who developed an SSI after laparotomy surgery was 0.05 at 7 days and 0.12 at 30 days (Table V) [35].…”
Section: Quality Of Lifementioning
confidence: 56%
“…EQ-5D scores demonstrated that SSIs negatively impact on patient HRQoL, demonstrated by a statistically significant reduction in HRQoL scores (11%) at 30 days in patients who underwent laparotomy surgery, relative to patients who did not develop an SSI [9]. It is noteworthy that the results of this study were also included in a recent systematic review by Gheorghe et al, who reported that the SSI utility decrement in patients who developed an SSI after laparotomy surgery was 0.05 at 7 days and 0.12 at 30 days (Table V) [35].…”
Section: Quality Of Lifementioning
confidence: 56%
“…Yet, they still represent a significant clinical and economic burden to the health care system [17][18][19][20][21]. In particular, wound infections are responsible for longer hospitalizations, increased costs for antibiotic therapy and topical wound care during the same admission and after discharge.…”
Section: The Economic and Clinical Burden Of Wound Infectionsmentioning
confidence: 99%
“…However, there are several observational studies and systematic reviews that analyzed the costs of robotic assisted prostatectomies or partial nephrectomies that can be used for our model [38,39]. Similarly, costs of treatment of surgical site infections [20], repair of incisional hernias [40], utility of patients undergoing incisional hernia repair [21] will be extracted from nontransplant scientific literature as we will assume that these values are applicable to our study population.…”
Section: Rationale For Cost-effectiveness and Cost-benefit Analysismentioning
confidence: 99%
“…The infection of an operated wound, especially in the case of arthroplasty or orthopedic implants, can have disastrous effects, the removal of the foreign material being necessary. Postoperative infections interrupt the normal healing process, increasing the risk of some associated pathologies or decompensation of the pre-existent ones, but also prolong the hospitalization time with significant additional costs for health systems [12][13][14].…”
Section: Introductionmentioning
confidence: 99%